Treatment outcomes among children and adolescents with extensively drug-resistant (XDR) and pre-XDR tuberculosis: Systematic review and meta-analysis. - Jayadeep Patra; Hyacinth Irving; Pranshu Maini; Jady Liang; Anwesh Patra; Mandar Paradkar; Jurgen Rehm (PLOS Global Public Health)
Extensively drug-resistant (XDR) and pre-XDR- tuberculosis (TB) account for approximately a third of pediatric MDR-TB cases globally. Clinical management is challenging; recommendations are based on limited evidence. We assessed the clinical outcomes for children and adolescents treated for XDR-and pre-XDR-TB. We performed a systematic review and meta-analysis of published studies reporting treatment outcomes for children and adolescents with XDR-and pre-XDR-TB. MEDLINE, EMBASE, Scopus, Web of Science, Google Scholar, and trial registries up to 31 December 2023 were searched. Eligible studies included children and adolescents aged <18 years with XDR-or pre-XDR-TB. The primary outcome was treatment success, defined as a composite of cure and treatment completion. Secondary outcomes were death, failure/ lost to follow-up and adverse events. We identified 34 population-based studies and 14 case studies, which reported treatment outcomes for a total of 656 patients. Treatment durations ranged from 6 to 27 months; follow-up after treatment completion ranged from 2 months to 4 years. The pooled estimate for treatment success in XDR-and pre-XDR-TB was 88·9% (95%CI: 59·7-100%) and 65·4% (95%CI: 27·7-100%), respectively. Drug adverse effects were reported in 56.4% (95%CI: 9.9-100%) and 68.2% (95%CI: 0-100%) of children respectively. Few childhood XDR- and pre-XDR-TB cases are reported. The relatively good treatment outcomes in children compared to adults may be partly due to publishing bias. Drug adverse effects are common.